2013
DOI: 10.1002/cphc.201200970
|View full text |Cite
|
Sign up to set email alerts
|

Significant Cation Effects in Carbon Dioxide–Ionic Liquid Systems

Abstract: Carbon dioxide–ionic liquid systems are of great current interest, and significant efforts have been made lately to understand the intermolecular interactions in these systems. In general, all the experimental and theoretical studies have concluded so far that the main solute–solvent interaction takes effect through the anion, and the cation has no, or only a secondary role in solvation. In this theoretical approach it is shown that this view is unfounded, and evidence is provided that, similarly to the benzen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 52 publications
4
80
0
2
Order By: Relevance
“…[32] Instead, it appears that, as in the case of LC-forming ILs and benzene, weaker cation-anion interactions allow the IL to act as ah ost network more easily and accommodate larger amountsoft he solute. While anions are correlatedw ith large changes in Henry's constants, it is the most weakly coordinating anion ([NTf 2 ] À ), whichg enerates the largests olubilities.…”
Section: Co 2 Solubilitymentioning
confidence: 99%
“…[32] Instead, it appears that, as in the case of LC-forming ILs and benzene, weaker cation-anion interactions allow the IL to act as ah ost network more easily and accommodate larger amountsoft he solute. While anions are correlatedw ith large changes in Henry's constants, it is the most weakly coordinating anion ([NTf 2 ] À ), whichg enerates the largests olubilities.…”
Section: Co 2 Solubilitymentioning
confidence: 99%
“…The second conformation is the on-top conformation, where the anion is above or below the ring center, see the ring and the side chain in gg or gt conformation of the same cation. 95,109,110,114,[118][119][120][121] To examine such coordination behavior, a combined distribution function containing the distance d CoR(+) − X(−) and the angle (r RN , r CoR(+) − X(−) ), where CoR(+) is the center of the imidazolium ring, RN is the ring normal of the same ring, and X(−) are the coordinating atoms of the anion, is employed. Representative CDFs are presented in Fig.…”
Section: E Cation-anion Interactionmentioning
confidence: 99%
“…[20][21][22] More recently, it was theoretically inferred that it is the introduction of neutral molecules like CO 2 in the IL charged network which cancels partially the charge-stabilizing effect existing in the neat IL and that this so-called inverse ionic liquid effect facilitates the carbene formation and, thus, the chemical absorption. 24,25 Very recently, new insights in the understanding of solute-solvent interactions within IL were provided from a theoretical study on the solvation of a carbene 1-ethyl-3-methylimidazole-2-ylidene in 1-ethyl-3-methylimidazolium acetate. 26 It was shown that the lack of strong hydrogen bonding between the hypovalent carbon atom of the carbene and the ring hydrogen atoms of the cation prevents the stabilization of this species explaining its high reactivity in acetate-based ILs.…”
Section: Introductionmentioning
confidence: 99%